Environmental Surveillance Reveals Complex Enterovirus Circulation Patterns in Human Populations. (1st October 2018) - Majumdar, Manasi; Sharif, Salmaan; Klapsa, Dimitra; Wilton, Thomas; Alam, Muhammad Masroor; Fernandez-Garcia, Maria Dolores; Rehman, Lubna; Mujtaba, Ghulam; McAllister, Gina; Harvala, Heli; Templeton, Kate; Mee, Edward T; et al.
Abstract: Background: Enteroviruses are common human pathogens occasionally associated with severe disease, notoriously paralytic poliomyelitis caused by poliovirus. Other enterovirus serotypes such as enterovirus A71 and D68 have been linked to severe neurological syndromes. New enterovirus serotypes continue to emerge, some believed to be derived from nonhuman primates. However, little is known about the circulation patterns of many enterovirus serotypes and, in particular, the detailed enterovirus composition of sewage samples. Methods: We used a next-generation sequencing approach analyzing reverse transcriptase polymerase chain reaction products synthesized directly from sewage concentrates. Results: We determined whole-capsid genome sequences of multiple enterovirus strains from all 4 A to D species present in environmental samples from the United Kingdom, Senegal, and Pakistan. Conclusions: Our results indicate complex enterovirus circulation patterns in human populations with differences in serotype composition between samples and evidence of sustained and widespread circulation of many enterovirus serotypes. Our analyses revealed known and divergent enterovirus strains, some of public health relevance and genetically linked to clinical isolates. Enteroviruses identified in sewage included vaccine-derived poliovirus and enterovirus D-68 stains, new enterovirus A71 and coxsackievirus A16 genogroups indigenous to Pakistan, and many strains from rarely reported serotypes. We show how this approach can be used for the early detection of emerging pathogens and to improve our understanding of enterovirus circulation in humans.